Sindicato em crise : dilemas, perspectivas e alternativas - Oliveira, Antônio José Xavier (2022)
The current scenery of brazilian union structure and its entities reverberates a crisis which results in the weakening and disruption of unions. Directly affected by the initiatives to dismantle social protection apparatuses, as well as by the negative consequences of the globalization process, these entities are going through a period of questioning and often erratic acting. The perspective that is found, although it is a worsening of the verified crisis, cannot be taken as a justification for the abandonment of these spaces of social interaction, agglutination of workers and, most importantly, of democratic participation and citizen formation. From the study of the factors that weaken these entities, this work analyzes the context of the constitutionalization of the union movement in the current brazilian legal order, highlighting the advances obtained with the constitutional text of 1988, but emphasizing the absence of incorporation, to the brazilian legal system, of full union freedom, understood as that disseminated by the International Labor Organization and materialized in its Convention 87/1948. From this, the scenarios of aggravation of this crisis will be presented, in particular the one observed from Law 13.467/17, as well as the existing alternatives, capable of renewing the forms of action of unions and other entities that make up the union structure. Thus, the research problem is delimited, based on the questioning about the existence of possible alternatives capable of reinvigorating the union's performance. Among the proposed solutions, approaches the way unions act in the face of the challenges posed by technological innovation, and the new forms of work arising from it, will be addressed. The following will be examined, in a special way: the possible alternatives of action of the unions in the regrouping of workers affected by technological innovation and in the reconstruction of the collective conscience; the possibility of social dialogue as a way of reinvigorating union activity in view of its importance for the improvement of democracy; the viability of collective bargaining on a transnational level; and, finally, the important role of unions in the possibility of collaborative action in defense of the primacy of human rights in companies. In this way, the present purposeful study, based on bibliographic research focused on the primary investigation of the pertinent legislation and on a logical-deductive approach to the detailed theme, promotes the analysis of such alternatives and points out ways for a reinvigorated union action.